2019
DOI: 10.3390/polym11122057
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Affinity Immobilization of Casein-Coated Silver Nanoparticles on Polymeric Membranes for Biofouling Control

Abstract: Silver nanoparticles (AgNPs) have been widely studied for the control of biofouling on polymeric membranes due to their antimicrobial properties. However, nanoparticle leaching has posed a significant impediment against their widespread use. In this study, a one-step method of chemically embedding AgNPs on cellulose acetate (CA) membranes via their affinity to thiol group chemistry was investigated. The operational efficiency of the membranes was then determined via filtration and biofouling experiments. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…In the study published by Dong et al [63], casein-coated AgNPs were embedded into acetate-cellulose membrane for control of biofouling. AgNPs effectively suppressed the growth of Serratia marcescens, and specifically, membranes with AgNPs displayed a decrease in microbial growth by 59-99% after this concentration was used [63]. Silver nanoparticles incorporated into the reverse osmosis membrane with a diameter of approximately 30 nm significantly reduced (by 64.6%) Pseudomonas sp.…”
Section: Agnps Immobilization Into Membrane and Composite Materialsmentioning
confidence: 99%
“…In the study published by Dong et al [63], casein-coated AgNPs were embedded into acetate-cellulose membrane for control of biofouling. AgNPs effectively suppressed the growth of Serratia marcescens, and specifically, membranes with AgNPs displayed a decrease in microbial growth by 59-99% after this concentration was used [63]. Silver nanoparticles incorporated into the reverse osmosis membrane with a diameter of approximately 30 nm significantly reduced (by 64.6%) Pseudomonas sp.…”
Section: Agnps Immobilization Into Membrane and Composite Materialsmentioning
confidence: 99%
“…Photo-induced free radical polymerization is a convenient method due to its short reaction time (minutes) and, unlike many controlled polymerizations, it does not require a catalyst or oxygen-free environment. A useful approach to introduce tailorable polymer brushes on a membrane surface is to graft poly(glycidyl methacrylate) from the membrane surface, then utilize the reactivity of the epoxide ring to add a functional group (Yune et al, 2012;Dong et al, 2019). Epoxide rings readily react with alcohols, amines, alkoxides, or Gringard agents, enabling the facile addition of binding groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that hydrophilic surface modification can be an effective method for reducing membrane fouling since the hydrophilic surface can repel foulant adsorption via the repulsive hydration force [ 5 ]. In addition, silver is widely known as a biocide and is used in numerous applications such as air filters, medicinal materials, drug delivery, textiles, water filtration, food packaging, and wastewater treatment [ 6 , 7 , 8 , 9 ]. Besides enhancing the membrane’s antimicrobial properties, silver is known to affect a membrane’s hydrophilicity as well.…”
Section: Introductionmentioning
confidence: 99%
“…Andrade et al embedded silver nanoparticles (AgNPs) into polysulfone nanofiltration membranes via the in-situ method and ex-situ method and found that the addition of silver onto the membrane’s surface reduced the contact angle of the membrane from 75.7° to 60.9° and increased the pure water flux of membranes from 25 to 121 L/m 2 h [ 10 ]. Optimization of the capture and stabilization of metals such as silver, which exhibits exceptional antimicrobial activity [ 7 , 8 , 11 , 12 ], has been a key focus for recent studies on filter substrate structure. For example, preventing Ag + from leaching into the permeate and causing loss of antimicrobial properties [ 13 ] is critical to silver’s effectiveness.…”
Section: Introductionmentioning
confidence: 99%